Comparative In Vitro Binding Studies of TiCl2(dpme)2, Ti(ada)2(bzac)2, and TiCl2(bzac)(bpme) Titanium Complexes with Calf-Thymus DNA - Pamita Awasthi; Nitesh Kumar; Raj Kaushal; Mohan Kumar; Shrikant Kukreti (Biochemistry Research International)
The binding of TiCl2(dpme)2 (1), (dpme = 6,6′-dimethyl-2,2′-bipyridine), Ti(ada)2(bzac)2 (2), (ada = adamantylamine; bzac = benzoylacetone), and TiCl2(bzac)(bpme) (3), (bpme = 4,4′-dimethyl-2,2′-bipyrdine) with calf thymus (ct) DNA has been studied by UV-visible spectroscopy, thermal denaturation, and circular dichroism spectroscopy. In UV-visible study complexes 1, 2, and 3 showed red, blue, and red shifts, respectively, upon the addition of ct-DNA along with a significant hyperchromism. The intrinsic binding constants (Kb) calculated from UV-visible absorption studies were 2.3 × 103 M−1, 3.3 × 103 M−1 and, 7.1 × 103 M−1 for complexes 1, 2, and 3, respectively. The change in melting temperature (ΔTm) was calculated to be 2-3°C for each complex. Circular dichroism (CD) study showed blue shift for complex 2 and red shift for complexes 1 and 3 along with rise in molecular ellipticity upon the addition of complexes. Results suggest a binding mode of complex 2 different than 1 and 3.